Preterm birth increases cerebral palsy hazards in children of mothers with chronic hypertension in pregnancy - Yi-Chien Huang; Hung-Chih Lin; Yu-Tzu Chang; Ming-Luen Tsai; Yu-Chia Chang; Lan-Wan Wang (Elsevier, 2024)
Background: Children of mothers with chronic-hypertension in pregnancy have high rates of preterm-birth (<37 weeks of gestation) and small-for-gestational-age (SGA), both of which are risk factors of cerebral palsy (CP). This study investigated the cumulative risks of CP in children exposed to maternal chronic-hypertension vs. other types of hypertensive-disorders-of-pregnancy (HDP), and whether preterm-birth and SGA potentiate the antenatal impact of chronic-hypertension to increase CP hazards. Methods: This population-based cohort study enrolled 1,417,373 mother-child pairs with singleton live births between 2004 and 2011 from the Taiwan Maternal and Child Health Database. A total of 19,457 pairs with HDP were identified and propensity-score-matched with 97,285 normotensive controls. Children were followed up for CP outcome until age 6-13 years. HDP were classified into chronic-hypertension, gestational-hypertension, preeclampsia, and preeclampsia-with-chronic-hypertension. Using the normotensive group as the reference, the associations between chronic-hypertension and CP hazard were assessed with adjusted hazard ratios (HR) and 95% confidence intervals (CI) in Cox proportional hazards regression models, and the effects of preterm-birth and SGA on the associations were examined. Results: The HDP group had higher rates of CP (0.8%) than the normotensive group (0.5%), particularly the subgroup of preeclampsia-with-chronic-hypertension (1.0%), followed by preeclampsia (0.9%), chronic-hypertension (0.7%) and gestational-hypertension (0.6%). Preterm-birth, but not SGA, exerted moderating effects to increase CP risks in children exposed to maternal chronic-hypertension. Before adjustments, chronic-hypertension alone had no substantial contribution to CP hazard (HR 1.35, 95% CI 1.00-1.83), while preeclampsia alone (1.64, 1.28-2.11) or with superimposed-chronic-hypertension (1.83, 1.16-2.89) had significant effects. After including preterm-birth in the multivariable model, the CP hazard for chronic-hypertension alone rather than other types of HDP was raised and became significant (1.56, 1.15-2.12), and the significance remained after stepwise adjustments in the final model (1.74, 1.16-2.60). Conclusions: Preterm-birth might potentiate CP hazards in children of mothers with chronic-hypertension in pregnancy.